Determination of U(VI) Using Sodium-Carbonate and Rhodamine-B as Ion-Associate by Flotation-Spectrofluorometric - Masrournia, M. (Asian Journal of Chemistry, 2011)
A simple and cost effective method for separation and preconcentration of U(VI) at the10-8 mol L-1 level in the environmental and mineral sample has been developed. The method is based on the flotation of uranyl-carbonate complex as an ion-associate with rhodamine-B at pH of 6.5 from a large volume of an aqueous solution (100 mL) using n-hexane. The floated layer was then dissolved in methanol for the subsequent spectrofluorometric determination. The detection limit (n = 5) was 6.5 × 10-8 mol L-1 and RSD (n = 6) obtained for 7 × 10-6 mol L-1 of U(VI) was 1.44 %. The interference effects of number of elements was studied and not found any interference. The proposed method was applied to determine of U(VI) in a synthetic wastewater and geological sample.